Research on mobility and conflict in the great lakes region/the case of the Hutu in Ituri (Uhamaji wa wanyerwanda: Migration and Conflict in Ituri, DR Congo, 2020)
This is the translation of a interview
Keywords: Land tenure; Migration; Social conflict; Conflict Theory